(untitled) (Research, Society and Development, 2025)
There is currently a growing demand for quality meat, and it is crucial to understand how different breeds respond to this technique in terms of reproductive performance. To analyze and describe the reproductive development of Nellore heifers crossed with Angus when they are subjected to Fixed-Time Artificial Insemination (FTAI), aiming to understand the reproductive performance and reproductive efficiency of the herd. Documentary research from direct sources, descriptive, qualitative and of the study or case report type. The 270 females selected and eligible for insemination were subjected to the IATF protocol between September and November 2024. The conception rate was assessed 30 days after insemination by means of transrectal ultrasound, where we obtained a result of 53.7% of pregnant cows, that is, 145 pregnant heifers after the first IATF protocol. Fixed-Time Artificial Insemination (IATF) has been consolidated as a strategic tool in beef cattle farming, especially when applied to the Nellore and Angus breeds. This reproductive biotechnology allows standardization of management, increased pregnancy rate in a shorter period of time, and rapid incorporation of superior genetics into the herd. IATF is a viable, efficient, and economically advantageous technology for production systems seeking greater productivity, standardization, and genetic advancement in the Nellore and Angus breeds.